The Effect of Transformational Leadership on Employee Job Satisfaction in the Chinese Retail Industry - Guo, Hexin (2019)
Abstract This dissertation is based on previous studies and aims to further the understanding of the extent of transformational leadership in a Chinese retail context, and examine its effects on the job satisfaction of employees. This can help in providing concise guidelines to enhance the implementation of transformational leadership in the retail sector in China. The researcher used quantitative research method to collected data form 181 employees from two retail Chinese companies (large and medium). The researcher used demographic analysis, ANOVA analysis, descriptive analysis, correlation analysis and regression analysis to analyse the research hypotheses. As for the prevalence of transformational leadership, results indicate it is a common practice at selected firms. The results demonstrated that transformational leadership, as a whole was associated with a positive impact on overall job satisfaction among employees in the two examined retail firms. Taken together, the research findings have made a significant and noteworthy contribution to the literature surrounding transformational leadership and its link to employees’ job satisfaction. Key words: Chinese Retail Industry, Transformational Leadership and Employee’s Job Satisfaction.